(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
Kazimierz Ajdukiewicz (1890–1963) was one of the eminent representatives of the Lvov-Warsaw School; his main interests were logic, theory of cognition, methodology of science and philosophy of language. The aim of the paper is to analyze selected problems concerning Ajdukiewicz’s concept of justification, in particular certain tensions and changes in his views on what can justify beliefs and assertions in science. The analysis is based primarily on Ajdukiewicz’s two volumes of papers, Język i poznanie [Language and Cognition], and his book, Problems and Theories of Philosophy. Ajdukiewicz’s views are discussed in the context of contemporary debates in Anglo-American epistemology concerning the dichotomy between internalism and externalism, as well as the role of epistemic individualism contrasted with epistemology of testimony and authority-based beliefs.